The Qur’anic Talut (Saul) and the Rise of the Ancient Israelite Monarchy - Nevin Reda (International Institute of Islamic Thought, 2008)
Using contemporary ideas of intertextuality, this study investigates the Qur’anic story of Talut (2:246-51), the first Israelite monarch, as it is set against the background of the Biblical account. A verse-by-verse analysis yields the Qur’anic sequence of events, which includes Talut’s nomination, the Ark’s appearance, crossing the river, Goliath’s defeat, and David’s succession. The Biblical counterparts, located within the books of Joshua, Judges, and I Samuel, feature such characters as Joshua, Gideon, Samuel, and Saul. The Qur’an is thereby reading the books of Joshua, Judges 6-8, I Samuel 1-7, and I Samuel 8-31 synoptically, and the Talut story is a harmonized account of these narratives. Reading between the two texts enhances the Qur’anic story, showing how it functions as a blueprint for the synoptic reading, in addition to furthering our understanding of Talut, who provides a typological prefiguration for Muhammad. However, the synoptic reading also enhances the Biblical story, showing the skill with which the multiple consecutive narratives implicitly argue for judgeship as opposed to kingship in the post-exilic context.